The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/nu13061959
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Metabolism in Chronic Alcohol-Use Disorder: Meta-Analysis and Systematic Review

Abstract: Chronic alcohol-use disorder has been imputed as a possible cause of dietary magnesium depletion. The purpose of this study was to assess the prevalence of hypomagnesemia in chronic alcohol-use disorder, and to provide information on intracellular magnesium and on its renal handling. We carried out a structured literature search up to November 2020, which returned 2719 potentially relevant records. After excluding non-significant records, 25 were retained for the final analysis. The meta-analysis disclosed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…These reports also suggested that supplementation of both Zinc and copper reversed the skin lesions and organ functions. The role of impaired kidney function in the development of magnesium deficiency among alcohol use disorder patients was recently reported [ 30 ]. Such studies impress that alcoholism-induced microelement deficiencies may be more prevalent than previously assumed.…”
Section: Discussionmentioning
confidence: 99%
“…These reports also suggested that supplementation of both Zinc and copper reversed the skin lesions and organ functions. The role of impaired kidney function in the development of magnesium deficiency among alcohol use disorder patients was recently reported [ 30 ]. Such studies impress that alcoholism-induced microelement deficiencies may be more prevalent than previously assumed.…”
Section: Discussionmentioning
confidence: 99%
“…31 At the same time, the recommended therapy of Mg depletion in patients with alcoholic liver cirrhosis does not significantly differ from that of other Mg-depleted patients. 13 According to a recent systematic review, 32 no study has thus far investigated the management of Mg depletion in chronic alcohol-use disorders. Hypomagnesemia is mostly mild presenting with minimal or no symptoms.…”
mentioning
confidence: 99%
“…33 This is one reason why oral supplementation is preferable. 32 Oral administration is safer, being associated with a lower risk of hypermagnesemia. 34 Intravenous replacement may be required for symptomatic cardiac arrhythmias such as torsade de pointes or neuromuscular irritability.…”
mentioning
confidence: 99%
“…A correlation between the reduction in both total and ionised circulating magnesium and chronic alcohol use disorder was also demonstrated by performing a meta-analysis [ 5 ]. In particular, inappropriately high magnesium excretion was reported in hypomagnesemic patients with chronic alcohol use disorder [ 5 ].…”
mentioning
confidence: 99%
“…A correlation between the reduction in both total and ionised circulating magnesium and chronic alcohol use disorder was also demonstrated by performing a meta-analysis [ 5 ]. In particular, inappropriately high magnesium excretion was reported in hypomagnesemic patients with chronic alcohol use disorder [ 5 ]. The major consequence of alcoholic or non-alcoholic liver disease is the accumulation of the extracellular matrix within the liver, leading to the development of cirrhosis.…”
mentioning
confidence: 99%